The effectiveness of using the two strategies of blended learning and flipped learning in the achievement of the tenth-grade high school students in the subject of Kurdish grammar. - Sarhan, Heevy; Nabi, Mawlood (Humanities Journal of University of Zakho, 2024)
The aim of the research is to identify the effectiveness of using the blended learning and flipped learning strategies in the achievement of the tenth-grade high school students in the subject of Kurdish grammar. The research community included tenth grade students from literary classes in day high schools for girls. There were (3319) students from the Semel Education Directorate in Semel district for the academic year (2021 – 2022). The sample included (81) students from (Shanaz for girls) and (Kumata for girls) high schools which were selected methodically. The participants for both the experimental and control groups were chosen randomly. The first experimental group consisted of (30) students, while the second experimental group consisted of (30) students from (Kumata high school for girls). On the other hand, the control group consisted of (21) students from (Shanaz high school for girls). The first experimental group used the blended learning strategy and the second experimental used the flipped leaning strategy, and the control group were using the usual method. The researchers prepared (8) daily plans for each method. The achievement test also included (35) ideas of multiple choiceand true and false questions. The validity of the test was extracted, analysis of variance for the test items and the level of difficulty for the test items, the discriminatory power of the test items, the effectiveness of the wrong alternatives, the duration of the test, and the stability of the test were calculated according to the equation (Kiodor- Richardson-20) of (0.90). After a full course, the experiment was completed. The researchers applied the tool, extracted data, and conducted statistical analysis using one-way analysis of variance (one-way ANOVA) and the Scheffe test. The results indicated that the blended learning strategy was more effective in academic achievement compared to both the flipped learning strategy and the usual method. Additionally, the flipped learning strategy showed greater effectiveness in academic achievement compared to the usual method.